Effect of the placement of rice in the domestic microwave oven on puffing characteristics of rice - Kumar, Ashok; Kulshrestha, Rewa (Journal of Postharvest Technology, 2023)
Puffed rice is a cheap, crispy and healthy popular snack product in India. Microwave oven can be used for puffing rice. The selection of puffing  zone and duration of heating influenced the puffing characteristics of rice grain. This paper studied the effect of placement of rice grain on the  turntable and microwave heating time on the puffing characteristics of the rice. The turntable (31.5 cm diameter) of the microwave oven was  divided into 12 puffing zones with each of 1.25 cm width and puffing characteristics were measured. The combination of puffing zone and  heating time was 3.75 to 5.0 cm puffing zones for 30 and 40 s heating time, and 2.5, 6.25 and 10.0 cm puffing zones for 50 S heating time, and  7.5 to 8.75 cm puffing zones for 60 S heating time. Slow rate of heating resulted in evaporative loss of moisture and hindered puffing process. Uniform rate of heating in case of sand bed puffing and non-uniform rate of microwave power absorption in case of microwave puffing was the  main reason for varying degree of puffing quality.
Keywords: Microwave puffing; , sand puffing; , percentage of puffing.